The role of women facilitators of bride kidnapping in Kyrgyzstan - Sadykova, Alina (Kansas State University, 2021)
The practice of kidnapping young women in Kyrgyzstan for forced marriage has existed for many years and has resulted in physical, psychological, and sexual violence against young women. Even though bride kidnapping has always been illegal, it has been routinely practiced throughout history. The process involves various actors at different stages, including a groom and his male friends, and his female and male relatives. The role of female relatives is significant in this process. By helping the groom, these women facilitate and contribute to the continuation of this illegal practice. Even though there is a growing body of literature on bride kidnapping, few studies have explored the roles of women facilitators of bride kidnapping. In fact, there is no study that specifically targets women facilitators, and little is known about their motives and perceptions of bride kidnapping. Knowing more about this topic is essential as bride kidnapping as it is practiced today could not continue without their involvement. As such, through a qualitative interview of women facilitators, my research is aimed at exploring the motivational factors and how these women facilitators understand their involvement in bride kidnapping and this practice in general. The study suggests six themes emerged based on the findings and provides recommendations for future research and policy.
Keywords: Bride kidnapping; Kyrgyzstan; Ceremony of persuasion; Kinship duty; Women facilitators